Labeling Monoclonal Antibodies with Metal Complexes: A Challenge for Coordination Chemists - Thomas A. Kaden (CHIMIA, 2000)
Three examples are used to show how the coordination chemist can develop macrocyclic ligands for labeling monoclonal antibodies used in nuclear medicine for tumor diagnosis and therapy.